Spontaneous nonsense mutation in the tuftelin 1 gene is associated with abnormal hair appearance and amelioration of glucose and lipid metabolism in the rat - Šilhavý, Jan; Mlejnek, Petr; Šimáková, Miroslava; Liška, František; Malínská, Hana; Marková, Irena; Hüttl, Martina; Miklánková, Denisa; Mušálková, Dita; Stránecký, Viktor; Kmoch, Stanislav; Sticová, Eva; et al. (Physiological genomics, 2024)
Recently, we have identified a recessive mutation, an abnormal coat appearance in the BXH6 strain, a member of the HXB/BXH set of recombinant inbred (RI) strains. The RI strains were derived from the spontaneously hypertensive rat (SHR) and Brown Norway rat (BN-Lx) progenitors. Whole genome sequencing of the mutant rats identified the 195875980 G/A mutation in the tuftelin 1 (Tuft1) gene on chromosome 2, which resulted in a premature stop codon. Compared with wild-type BXH6 rats, BXH6-Tuft1 mutant rats exhibited lower body weight due to reduced visceral fat and ectopic fat accumulation in the liver and heart. Reduced adiposity was associated with decreased serum glucose and insulin and increased insulin-stimulated glycogenesis in skeletal muscle. In addition, mutant rats had lower serum monocyte chemoattractant protein-1 and leptin levels, indicative of reduced inflammation. Analysis of the liver proteome identified differentially expressed proteins from fatty acid metabolism and β-oxidation, peroxisomes, carbohydrate metabolism, inflammation, and proteasome pathways. These results provide evidence for the important role of the Tuft1 gene in the regulation of lipid and glucose metabolism and suggest underlying molecular mechanisms.NEW & NOTEWORTHY A new spontaneous mutation, abnormal hair appearance in the rat, has been identified as a nonfunctional tuftelin 1 (Tuft1) gene. The pleiotropic effects of this mutation regulate glucose and lipid metabolism. Analysis of the liver proteome revealed possible molecular mechanisms for the metabolic effects of the Tuft1 gene.
Keywords: Animals; zánět; potkani inbrední BN; proteom; tuftelin 1 gene; Codon, Nonsense; Proteome; Lipid Metabolism; Rats, Inbred BN; Insulin; lipid and glucose metabolism; Tuft1; metabolismus lipidů; rat; Inflammation; nesmyslný kodon; hepatic proteome; glukosa; Glucose; krysa rodu Rattus; potkani inbrední SHR; zvířata; spontaneous nonsense mutation; inzulin; Rats; Rats, Inbred SHR